(untitled) (Confluenţe Bibliologice, 2026)
In this article, the author examines how to be a librarian from Comunication Collection Department, what qualities should be inherent to it, how should behave in communicating with users during the service, what rules of etiquette must be followed. As the research object was taken home lending room number two Methodical/didactic literature of the Alecu Russo University Scientiﬁc Library.